Estudo das propriedades farmacológicas da resina de Protium heptaphyllum (Aubl) March e de seus principais constituintes, mistura de alpha e beta amirina - Oliveira, Francisco de Assis (2005)
Protium heptaphyllum March (Burseraceae) populary known as “almécega” is a popular medicinal plant largely encountered in the Amazon region, various States of Brazil and in several South American Countries. The oily amorphous exudate obtained from this plant is widely used in skin diseases, healing of ulcers, and as an analgesic and anti-inflamatory agent. Phytochemical studies reveled the presence of several monoterpenes and pentacyclic triterpenes such as a mixture of α- e β – amyrin, maniladilol and breine. The present study aimed to investigate the general toxicity and to establish the pharmacological activity of resin and is major triterpenoid mixture, the α and β – amyrin. In toxicity tests, both the resin and triterpene mixture exhibited low toxicity to mice. Resin at doses up 5 g/kg, (p.o.) or 2 g/kg (i.p.) and triterpene mixture up to 3 g/kg, (p.o.) or 2 g/kg (i.p.) failed to induce any mortality in mice. In Artemia-lethality test, the calculated (probit analysis) CL50 values for resin and triterpenes were in the order of 42,54 ± 19,96 and 400 ± 27,85 μg/mL, respectively. In pharmacological tests, the resin was analysed for anti-inflamatory (carrageenan-induced edema, cotton pellet-induced granuloma, and vascular permeability increase induced by i.p. acetic acid) and gastroprotective (absolute ethanol and acidified ethanol) effects, whereas the triterpene mixture was examined in assays that demostrate gastroprotective (against lesions induced by absolute ethanol), antipruritus (against pruritus induced by Dextran T40 and compound 48/80), acute and visceral antinociceptive (test of subplantar and intracolonic capsaicin) and hepatoprotective (against acetaminophen- and Ga1N/LPS-induced models of hepatitis) effects. In anti-inflammatory test, the resin (200 e 400 mg/kg, p.o.) although failed to modify the carrageenan-induced acute rat paw-edema response, it caused signficant inhibitions at a dose of 400mg/kg on the formation of cotton pellet-induced granulomas and on the vascular permeability increase induced by i.p. acetic acid in mice. In addition, the (200 e 400 mg/kg) showed gastroprotective potential against absolute- and acidified ethanol- induced gastric lesions as evidenced from siginificant diminution in lesion scores, restoration of the ethanol-induced depletion of non-protein sulfhydryl content More over, the resin demonstrated an antisecretory effect on gastric acid secretion induced in 4-h pylorus ligated rats. The triterpene mixture also produced similar gastroprotection against ethanol-induced lesions in a manner similar to capsaicin, a pungent principle from hot peppers. This protection possibly involves capsaicin-sencitive primary afferents since it was abolished in mice pretreated with a neurotoxic dose of capsaicin. The α and β – amyrin mixture (100 mg/kg) manifested antipruritus effect as evidenced from suppression of scratching behaviour in the mouse model of prurits induced by s.c. injections of dextran T40 and compound 48/80. Besides, it also produced an antiedematogenic effect in model of hind paw edema induced by histamine, compound 48/80 and dextran T40 and markedly depressed the compound 48/80-elicited rat mast cell degranulation (ex vivo). An antinociceptive effect of triterpenoid mixture (3-100 mg/kg) was observed in capsaicin-evoked somatic (1.6 μg/site, suplantar) and visceral (149 μg, intracolonic) models of nociception in mice. Greater suppression of nociceptive behaviors were evidenced at a dose of 10 mg/kg α and β – amyrin mixture, which mimicked the effect produced by ruthenium red, a non-competitive capsaicin antagonist. The antinociceptive effect of triterpenoid mixture was found to be naloxone (2 mg/kg)- sensitive, suggesting an opioid mechanism. A blockade by triterpene mixture was also evidenced on the hyperthermic but not the hypothermic response of subcutaneously administered capsaicin (10 mg/kg) suggesting possible incolvement of TRPV1 receptor. In open-field and rota-rod tests, the triterpene mixture did not manifest signs of either sedation or motor abnormality in mice that could account for the observed antinociception. In the model of acetaminophen (500 mg/kg)-induced hepatotoxicity, the triterpenoid mixture (50 and 100 mg/kg) effectively reduced the elevated serum AST and ALT levels, restored the depleted GSH and markedly diminished the histopathological alterations. Potentation of pentobarbital-sleeping time was, however observed at these doses of triterpenoid, incidating a probable suppression of cytochrome P450 and thus a diminished metabolite formation that may account for reduced acetaminophen toxicity. The α- and β – amyrin mixture offered complete protection against the mortality associated with Ga1N/LPS , but caused only a moderate diminution of serum enzymes and histopathological alterations. Taken together, these findings show that the resin and α- and β – amyrin mixture possess low toxicity and have a wide therapeutic potential with anti-inflammatory, antinociceptive, antipruritus, and gastro- and hepato-protective actions. Most of the effects of triterpenoid mixture appear to involve in part the participation of primary sensory afferents in their actions.